Condition of Coral Reef Cover and Overview of Coral Fish in Pagang Island, South Coast, West Sumatera - Sirait, Juliper Parasian; Siregar, Sofyan Husein; Nedi, Syahril (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in October 2020 in the waters of Pagang Island, Koto XI Tarusan District, South Coast Regency, West Sumatera Province. This study aims to determine the condition of coral reefs and reef fish in coral reef ecosystems which were analyzed based on the coral cover in Pagang Island. The method used in this research is UPT (Underwater Photo Transect) for assessing the live coral coverage and the UVC (Underwater Visual Census) for collecting the reef fishes data. The result shows that the condition of coral reef cover in Pagang Island at all stations is in critical condition. However, the high percentage of coral dying at all stations presumed that these coral reefs were in good condition. Percentage of coral cover in the station I 4.13%, station II 6.2%, station III 1.2%, and station IV 2.07%. A total of 31 fish species belonging to 7 families with a total of 328 individuals were identified in all stations. The average abundance of fish at all stations is 0.328 ind/m2.